Getting Laid and Growing Close: Constructions of Masculinity in Relationship Advice for Heterosexual Men - Knudson, Sarah (Qualitative Sociology Review, 2014)
Despite the growing popularity of men’s self-help products, recent debates surrounding hegemonic masculinity, and attention to the “crisis of masculinity,” research has ignored men’s advice about intimate relationships. Consequently, I examine 30 contemporary relationship advice books and conceptualize their constructions of heterosexual masculinity. Findings demonstrate authors’ overall rejection of hegemonic masculinity, alongside an overarching strategy of “masculinizing” intimacy that promotes two subsidiary gender strategies – relational heroism and tempered ambition – which reframe non-hegemonic behavior as manly. The overarching strategy appears in mild forms in books emphasizing “getting laid” and stronger variants in books that promote “growing close” through intimacy. The strategy promotes a promising departure from the constraints of hegemonic masculinity by broadening men’s acceptable range of talking about and doing masculinity, but continues to emphasize gender difference and enables a reconfiguration of heterosexual masculine intimacy within hegemonic masculinity, thereby limiting its promotion of gender equality.